Herpes Simplex Virus Laryngitis Presenting as Airway Obstruction: A Case Report and Literature Review. (May 2017) - Harless, Lucas; Jiang, Nancy; Schneider, Frank; Durr, Megan
Objectives: Herpes simplex virus (HSV) laryngitis is rare in adults. We add a case report to the literature and perform a literature review to further delineate the clinical presentation, course, and treatment of HSV laryngitis in adults. Methods: Case report and literature review using PubMed and Ovid databases. Results: Ten cases of diagnosed HSV laryngitis in adults were reported in the literature. It is more common in immunocompromised patients. The mean patient age was 51 years with a male to female ratio of 1:1. The clinical presentation and course of HSV laryngitis is variable. Patients may have mild chronic symptoms, such as dysphonia, or a fulminant course with rapid airway compromise. On laryngoscopic exam, the most common findings are a white exudate or ulceration. The most common treatment is with antiviral medication, such as acyclovir, which tends to be highly effective. Conclusions: Herpes simplex virus laryngitis is rare. Clinical presentation of HSV laryngitis is variable, and its course may be indolent or fulminant. Treatment with antiviral medication tends to be highly effective.